Direct observation of multiple conduction-band minima in high-performance thermoelectric SnSe. (15th January 2023) - Okawa, Mario; Akabane, Yuka; Maeda, Mizuki; Tan, Gangjian; Zhao, Li-Dong; Kanatzidis, Mercouri G.; Suzuki, Takeshi; Watanabe, Mari; Xu, Jiadi; Ren, Qianhui; Fujisawa, Masami; Kanai, Teruto; et al.
Graphical abstract: Abstract: We report time- and angle-resolved photoemission spectroscopy on SnSe which currently attracts great interest due to its extremely high thermoelectric performance. Laser-assisted photoemission signals are observed within ± 20 fs of the pump pulse arrival. Around 30–50 fs after the photoexcitation, the conduction band minima are not populated by the photoexcited electrons while the valence bands are considerably broadened. In going from 90 fs to 550 fs after the photoexcitation, the photoexcited carriers are decayed into the multiple conduction band minima. The observed conduction bands are consistent with the band structure calculations. The multiple conduction minima suggest possibility of high and anisotropic thermoelectric performance of n -type SnSe single crystal if it is realized.